Strategy Analysis Of Potential For The Development And Development Of BKMF Basic Achievements In FIK UNM - Nurul Fitriani; Herman Herman; Muslim Muslim (UNIVERSITAS NEGERI MAKASSAR, 2022)
This research is a qualitative descriptive study that aims to find out how the Potential Strategy for the Development and Development of Achievement Sports in the Faculty of Sports Science. The number of informants in this study was students as well as administrators of BKMF Badminton FIK UNM. Data collection techniques through observation methods, interview methods, and documentation methods. Data analysis techniques in this study used data reduction techniques, data presentation, and conclusions. The results showed that the Potential Strategy for Development and Development of Achievement Sports in the Faculty of Sports Science from the indicators of the accuracy of the program targets was a good Potential Strategy for Development and Development of Achievement Sports, this was seen from the organizational work system. Based on the development strategy with an important influence by the coach who has directed athletes to take part in badminton matches both within the campus and outside the campus, with various training programs, such as tactical, physical or weight training exercises, and interspersed with motivation. Likewise, the organizational performance carried out at BKMF Badminton is running well and right on the target, namely sports achievements, seen from professional coaches in training and always well and firmly behaved to their athletes without discriminating between athletes.